The right to reproduction - The right to abortion - Stanescu, Nina (Technium Social Sciences Journal, 2021)
As for the attitude towards abortion, over time, it has fluctuated from one era to another. Thus, the ancient societies of Greece and Rome were tolerant of abortion, and with the Romans abortion could be performed at any time during pregnancy. One of the aspects that received special attention was the right of women to have a say in their own reproduction, namely the right of women to choose whether or not to keep a pregnancy, Immoral in terms of of the Church, outlawed by the legislation of some states, the right to abortion has had a sinuous evolution in the social scene of many states. This issue has many political, moral and social connotations, being politically regulated differently by different states. The extremes are represented on the one hand by China, which pursues a policy of limiting population growth, including through a pro-abortion policy and on the other hand by Islamic states, in which abortion for therapeutic purposes and on-demand abortion are prohibited. In Europe, most states have legalized abortion, but at the same time apply policies to limit it, by promoting family planning and contraceptive methods.